Oxidizing substrate specificity of Mycobacterium tuberculosis alkyl hydroperoxide reductase E: kinetics and mechanisms of oxidation and overoxidation - Reyes, Aníbal M (2011)
Alkyl hydroperoxide reductase E (AhpE), a novel subgroup of the peroxiredoxin family, comprises Mycobacterium tuberculosis AhpE (MtAhpE) and AhpE-like proteins present in many bacteria and archaea, for which functional characterization is scarce. We previously reported that MtAhpE reacted ~ 103 times faster with peroxynitrite than with hydrogen peroxide, but the molecular reasons for that remained unknown. Herein, we investigated the oxidizing substrate specificity and the oxidative inactivation of the enzyme. In most cases, both peroxidatic thiol oxidation and sulfenic acid overoxidation followed a trend in which those peroxides with the lower leaving-group pKa reacted faster than others. These data are in agreement with the accepted mechanisms of thiol oxidation and support that overoxidation occurs through sulfenate anion reaction with the protonated peroxide. However, MtAhpE oxidation and overoxidation by fatty acid-derived hydroperoxides (~ 108 and 105 M− 1 s− 1, respectively, at pH 7.4 and 25 °C) were much faster than expected according to the Brønsted relationship with leaving-group pKa. A stoichiometric reduction of the arachidonic acid hydroperoxide 15-HpETE to its corresponding alcohol was confirmed. Interactions of fatty acid hydroperoxides with a hydrophobic groove present on the reduced MtAhpE surface could be the basis of their surprisingly fast reactivity.